Foliar Application of Copper Oxide Nanoparticles Suppresses Fusarium Wilt Development on Chrysanthemum. - Elmer, Wade H; Zuverza-Mena, Nubia; Triplett, Lindsay R; Roberts, Elizabeth L; Silady, Rebecca A; White, Jason C (Environmental science & technology, 2021)
Micronutrients applied as nanoparticles of metal oxides have shown efficacy in vegetable and other crops for improving yield and reducing Fusarium diseases, but their role in ornamental crop management has not been investigated. In 2017, 2018, and 2020, nanoparticles of CuO, Mn2O3, or ZnO were foliarly applied at 500 mug/mL (0.6 mg/plant) to chrysanthemum transplants and planted in potting soil noninfested or infested with Fusarium oxysporum f. sp. chrysanthemi. An untreated control and a commercial fungicide, Fludioxonil, was also included. Chrysanthemums treated with nanoscale CuO had a 55, 30, and 32% reduction in disease severity ratings compared to untreated plants in 2017, 2018, and 2020, respectively. Specifically, the average dry biomass for the three years was reduced 22% by disease, but treatment with nanoscale CuO led to a 23% increase when compared to controls. Similar trends with plant height were observed. Horticultural quality was improved 28% with nano CuO and was equal to the fungicide. Nanoscale Mn2O3 and the fungicide did not consistently reduce disease ratings or increase dry biomass each year. Nanoscale ZnO was ineffective. Nanoscale CuO-treated plants had 24 to 48% more Cu/g tissue than controls (P < 0.001). These findings agree with past reports on food crops where single applications of nanoscale CuO improved plant health, growth, and yield and could offer significant impacts for managing plant diseases on ornamentals.
Keywords: *Chrysanthemum; *Fusarium; *Metal Nanoparticles; *Nanoparticles; Article; Chrysanthemum; Copper; Copper oxide nanoparticles; Copper oxides; Crops; Disease ratings; Disease severity; Foliar application; Fungi; Fungicides; Fusarium; Fusarium oxysporum f. sp. chrysanthemi; Fusarium oxysporums; Fusarium wilt; II-VI semiconductors; Manganese oxide; Metal Nanoparticles; Metal nanoparticles; Nanoparticles; Nanoscale ZnO; Ornamental crops; Oxide minerals; Oxides; Soils; Untreated control; Zinc oxide; biomass; comparative study; controlled study; copper; copper oxide nanoparticle; crop protection; dept.bio; disease severity; elemental analysis; filamentous alga; foliage; food crop; gene; growing season; horticultural species; horticulture; hydrodynamics; metal nanoparticle; nanoparticle; nonhuman; oxide; peer-reviewed; plant disease; plant growth; plant height; plant tissue; trace element; wilt

Plant-engineered ZnO and CuO nanoparticles exhibit pesticidal activity and mitigate Fusarium infestation in soybean: A mechanistic understanding - Karmous, Inès; Elmer, Wade; Zuverza‐Mena, Nubia; Vaidya, Shital; Tlahig, Samir; Scanley, Jules; Bharadwaj, Anuja; White, Jason; Dimkpa, Christian (Plant Physiology and Biochemistry, 2025)
Keywords: Antifungal activity; Artemisia vulgaris; Biogenic copper and Zn oxide nanoparticles; Biology; Botany; Chemistry; Fusarium; Infestation; Materials science; Nanoparticle; Nanotechnology; Soybean; dept.phy; peer-reviewed